Patent Law and Women, Tackling Gender Bias in Knowledge Governance - Nair, Aradhana (Christ University Law Journal, 2022)
Jessica. C. Lai, Routledge, Taylor and Francis group,Routledge, 2022, [ISBN No: 978-0-367-65227-2] People often tend to think that Intellectual property laws should not be judged through the gender lens as they are more technical and objective in nature. Will gender be a matter of importance in technical aspects like intellectual property, specifically patent, is something which many of us wonder. Research in the area of patents as to know the reason why there is a dearth of women inventors as compared to the male counterparts, or do the women inventors actually face issues before the grant of patent or how far have the women inventors been successful in utilising the patent granted to them – all these come under the purview of discussion in Jessica’s book. World Intellectual Property Organization (WIPO) had reported that the ratio of male inventors is higher than women at the international level. These observations were the reasons that the book was referred to. It is a well researched work that deals with gender biases in knowledge governance.